Психологічний опис переживань у професійний діяльності поліції - Пономаренко, Я. С.; Ponomarenko, Ya. S.; Пономаренко (Посохова) Яна Сергіївна (Габітус. - 2023. - Вип. 46. - С. 238-242, 2023)
Презентовано теоретичний огляд та емпіричне дослідження професійних переживань у практиці поліціювання. Представлено специфіку та психологічні наслідки переживань у діяльності поліції. Розглянуто наукові доробки українських та закордонних учених, які надають професійним переживанням центральне місце як на етапі підготовки, так і в період професійної діяльності поліцейських. Професійні переживання поліцейських є закономірними реакціями на стресори, котрі можуть призвести до емоційного виснаження, деперсоналізації та стагнації. Виявлено особливості професійних переживань у поліцейських із різним рівнем особистісно-професійної здійсненності та з урахуванням їхніх гендерних розбіжностей.

The article presents a theoretical overview and empirical study of professional experiences in the practice of policing. The specifics and psychological consequences of experiences in police activities are presented. The scientific developments of Ukrainian and foreign scientists, which give professional experiences a central place both at the stage of training and during the professional activity of police officers, are considered. Professional experiences of police officers are natural reactions to stressors that can lead to emotional exhaustion, depersonalization and stagnation. The purpose of the study was to identify and describe the characteristics of professional experiences of police officers with different levels of personality's-professional fulfillmentity (PPF) and taking into account their gender differences. The study sample consisted of 240 people, of whom 120 were women and 120 were men. With the use of the author's questionnaire « Diagnostics of the personality's-professional fulfillmentity of police officers», three groups were formed according to the levels of PPF: low, medium and high. In the group of women, a low level was diagnosed in 28 people, an average level in 55, and a high level in 37 women. Men were distributed as follows: low level in 29 people, medium in 49 and high in 42 respondents. The mean level of PPF was excluded from further study. To achieve the goal, the technique «Experiences in Activity Questionnaire (EAQ)» was involved. Empirical study of professional experiences of female and male police officers demonstrated the peculiarity of the functioning of the studied phenomenon in the specified groups. Female police officers with a low level of PPF have a more pronounced feeling of emptiness, while women with a high level have indicators of satisfaction and meaning. Representatives of the first group feel emotional devastation, while women with a high level of PPF, despite the complexity of the work, are able to enjoy their work. In the group of male policemen with a low level of PPF, the indicator of effort dominates, in relation to men with a high level of PPF, they are characterized by indicators of satisfaction and meaning. This means that officers with a low level of PPF are forced to exert more effort during operational tasks, and police officers of the second group skillfully overcome the challenges of the profession and realize the meaning of their actions. Based on a qualitative analysis of the professional experiences of the entire sample, it was established that more than 50% of the respondents are satisfied with their profession, 60% understand the meaning of their activities. More than half of the respondents are forced to make efforts to maintain productivity and ensure effectiveness, and only 30% of respondents have a sense of devastation.

Представлен теоретический обзор и эмпирическое исследование профессиональных переживаний в практике полицейского. Представлены специфика и психологические последствия переживаний в деятельности полиции. Рассмотрены научные достижения украинских и зарубежных ученых, которые предоставляют профессиональным переживаниям центральное место как на этапе подготовки, так и в период профессиональной деятельности полицейских. Профессиональные переживания полицейских являются закономерными реакциями на стрессоры, которые могут привести к эмоциональному истощению, деперсонализации и стагнации. Выявлены особенности профессиональных переживаний у полицейских с разным уровнем личностно-профессиональной осуществимости и с учетом их гендерных различий.
Psychological description of experiences in the professional activities of the police
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; поліція; police; полиция; поліцейські; police officers; полицейские; особистісно-професійна здійсненність; personal and professional feasibility; личностно-профессиональная осуществимость; професійна діяльність; professional activity; профессиональная деятельность; професійні переживання; professional experiences; профессиональные переживания; гендер; gender